Molecular patterns of multidrug resistance of Mycobacterium tuberculosis in Georgia - N Shubladze (International Journal of Mycobacteriology, 2013)
Background: Tuberculosis (TB) infections caused by multidrug-resistant Mycobacterium tuberculosis (MDR MTB) remain a significant public health concern worldwide. Georgia has a high prevalence of MDR MTB. The genetic mechanisms underlying the emergence of MDR MTB strains in this region are poorly understood and need to be determined for developing better strategies for TB control. This study investigated the frequency of major drug resistance mutations across rpoB, katG and inhA loci of Georgian MDR MTB strains and explored differences between new and previously treated patients. Methods: A total of 634 MTB strains were examined for which an MDR phenotype had been previously determined by the proportions method. The GenoType®MTBDRplus system was applied to screen the strains for the presence of rpoB (S531L, H526D, H526Y, and D516V), katG (S315T) and inhA promoter region (C15T and T8C) mutations. The target loci were amplified by PCR and then hybridized with the respective site-specific and wild type (control) probes. Results: Out of the 634 isolates tested considered by phenotypic testing to be resistant to RIF and INH, this resistance was confirmed by the GenoType®MTBDRplus assay in 575 (90.7%) isolates. RIF resistance was seen in 589 (92.9%) and INH resistance was seen in 584 (92.1%); 67.2% and 84.3% of MDR strains harbored respectively rpoB S531L and katG S315T mutations (generally known as having low or no fitness cost in MTB). The inhA C15T mutation was detected in 22.6% of the strains, whereas rpoB H526D, rpoB H526Y, rpoB D516V and inhA T8C were revealed at a markedly lower frequency (≤5.2%). The specific mutations responsible for the RIF resistance of 110 isolates (17.4%) could not be detected as no corresponding mutant probe was indicated in the assay. There was no specific association of the presence of mutations with the gender/age groups. All types of prevailing mutations had higher levels in new cases. Conclusions: A great majority of the Georgian MDR MTB strains have a strong preference for the drug resistance mutations carrying no or low fitness cost. Thus, it can be suggested that MDR MTB strains with such mutations will continue to arise in Georgia at a high frequency even in the absence of antibiotic pressure.